2023
DOI: 10.1029/2022rg000791
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic Process Chains in High‐Mountain Regions—A Review and Classification Approach for Natural Hazards Assessment

Peter Mani,
Simon Allen,
Stephen G. Evans
et al.

Abstract: Populations and infrastructure in high mountain regions are exposed to a wide range of natural hazards, the frequency, magnitude, and location of which are extremely sensitive to climate change. In cases where several hazards can occur simultaneously or where the occurrence of one event will change the disposition of another, assessments need to account for complex process chains. While process chains are widely recognized as a major threat, no systematic analysis has hitherto been undertaken. We therefore est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 208 publications
0
3
0
Order By: Relevance
“…Sedongpu CGHC is a geomorphic process chain (Mani et al., 2023), different from ordinary landslides or debris flows (Gnyawali et al., 2020). Initially, a rock‐ice avalanche occurred at an altitude of 6,200 m when the hanging glacier failed.…”
Section: Discussionmentioning
confidence: 99%
“…Sedongpu CGHC is a geomorphic process chain (Mani et al., 2023), different from ordinary landslides or debris flows (Gnyawali et al., 2020). Initially, a rock‐ice avalanche occurred at an altitude of 6,200 m when the hanging glacier failed.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have not revealed the entire process and mechanism of the formation, development, evolution, and hazard-causing of the MLG debris flow hazard chain under the internal and external dynamic coupling. Unlike the simple superposition of single or multiple hazards, the mountain hazard chains often have temporal and spatial continuity and extension, and exhibit cascading and compound effects, often characterized by huge damage, wide impact range, and long duration (Chen and Cui, 2017;Mani et al, 2023). With the acceleration of economic development and population growth, engineering activities in mountainous urban areas in western Sichuan are also increasing rapidly (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Situated in the collision zone between the Eurasian Plate and the Indian Ocean Plate, the Hengduan and the Himalayan Mountains possess a complex geological environment with active geological movements, resulting in numerous types of geohazards and cascading geohazards. Among them, cascading processes triggered by landslides and rockfalls are the most typical in the region [2][3][4], such as the "landslide-debris flow-river blockage" 2 of 18 cascade in Sindupalchowk, Nepal, in 2014 [5]; the "landslide-debris flow-dammed lakebreach flood" cascade in Tibet, China, in 2018 [6]; and the "earthquake-landslide/rockfalldammed lake-flood" cascade in Kukrekhola, Nepal, in 2018 [7]. In the Latudi River valley, a tributary of the Nujiang River in the Hengduan Mountains, the geological environment is fragile.…”
Section: Introductionmentioning
confidence: 99%